2013
DOI: 10.1111/pace.12319
|View full text |Cite
|
Sign up to set email alerts
|

Protection from Outpatient Sudden Cardiac Death following ICD Removal Using a Wearable Cardioverter Defibrillator

Abstract: WCD can prevent SCD, until ICD reimplantation is feasible in patients who underwent device removals for CDI. However, patient compliance is essential for the effective use of this device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 24 publications
0
28
2
Order By: Relevance
“…Wearable cardioverter‐defibrillator (WCD) is an external device that monitors health rhythm continuously and delivers an electric shock when ventricular arrhythmia (ventricular tachycardia or ventricular fibrillation) is detected. A clinical study showed promising findings that the WCD prevented SCD in patients with temporary ICD removal . Data from the Prospective Registry of Patient Using the Wearable Defibrillator (WEARIT‐II) Registry demonstrated a high rate (3% for 3 months) of sustained ventricular tachyarrhythmia at high‐risk patients, and suggested WCD to be safe and effective in protecting patients at risk of SCA .…”
Section: Introductionmentioning
confidence: 99%
“…Wearable cardioverter‐defibrillator (WCD) is an external device that monitors health rhythm continuously and delivers an electric shock when ventricular arrhythmia (ventricular tachycardia or ventricular fibrillation) is detected. A clinical study showed promising findings that the WCD prevented SCD in patients with temporary ICD removal . Data from the Prospective Registry of Patient Using the Wearable Defibrillator (WEARIT‐II) Registry demonstrated a high rate (3% for 3 months) of sustained ventricular tachyarrhythmia at high‐risk patients, and suggested WCD to be safe and effective in protecting patients at risk of SCA .…”
Section: Introductionmentioning
confidence: 99%
“…Lack of compliance might have dramatics consequences. Indeed, in various studies, the majority of SCD observed during follow-up were observed in patients not or not-correctly wearing the WCD[7,8]. Weight and footprint of the device were the main reasons for low compliance.…”
Section: Patient Education and Compliancementioning
confidence: 99%
“…Period before re-implantation is long, so that patients could beneficiate from WCD protection without deleting hospital discharge, as the risk of SCD remains unchanged[7] during this period. Highest incidence rate of appropriate therapies remains to patients after ICD explantation for infection in expectation of reimplantation compared with other indications[14].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Recent trials demonstrated the efficacy of the WCD in the detection and treatment of lethal ventricular arrhythmias [57], [61]. The WCD therapy can prevent SCD until ICD re-implantation is feasible in patients who underwent device removals for device system infections [62].…”
Section: New Technology To Reduce the Risk Of Sudden Cardiac Death Afmentioning
confidence: 99%